O trabalho da mulher e a proteção a maternidade - Coelho, Nicolau Rafael Guimarães (2017)
The objective of the present study is the analysis of a current topic of great relevance, namely, women's work and maternity, according to the current legal system. For this approach, it is necessary to highlight the dual role that women play in society, either as a worker in search of capital for the support of her family and as administrator of the home, and to provide means of subsistence in the first moments of the new life that was Conceived. Thus, there is no denying the need to reassess the role of motherhood, given the increased participation of women in the labor market. Including women in the labor market goes far beyond their qualification, just as men do. It means respecting their hormonal, personal and family characteristics, where maternity is highlighted, as it is a general knowledge of the difficulty of reconciling responsibilities arising from the labor market and the obligations arising from maternity. Despite the adverse scenario of maternity and the economic crisis in Brazil, the transition and increase in the number of women entering and remaining in the Brazilian labor market is perceptible. It should be noted that a brief analysis of statistics reveals that men still have higher wages, which demonstrates a discriminatory nature of the insertion of women into the labor market. On the other hand, there is an increase in female employment in middle-level qualification occupations, with relatively more compensated income, with labor benefits extended by the Federal Constitution of 1988, and supported by the Consolidation of Labor Laws (CLT) As in several activities that historically have always been occupied by the male sex, such as, engineering, drivers, among others